2001
DOI: 10.1254/jjp.85.175
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-inflammatory Effect of FR188582, a Highly Selective Inhibitor of Cyclooxygenase-2, With an Ulcerogenic Sparing Effect in Rats

Abstract: ABSTRACT-The anti-inflammatory and ulcerogenic effects of FR188582, 3-chloro-5-[4-(methylsulfonyl) phenyl]-1-phenyl-1H-pyrazole, were investigated. In a recombinant human cyclooxygenase (COX) enzyme activity, FR188582 inhibited COX-2 with an IC50 value of 0.017 mM, and the inhibition of prostaglandin (PG) E2 formation by FR188582 was over 6000 times more selective for COX-2 than COX-1. Oral administration of FR188582 dose-dependently inhibited adjuvant arthritis. This effect was threefold more potent than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Examples of central heterocycles include 5-or 6-membered rings that contain one (thiophenes [35][36][37], pyrroles [59][60][61], furans [62,63] and pyridines Pyrroles Eurans 2(5H)-Furanones Thiazo1es 21 [64][65][66]), two (thiazoles [67,68], oxazoles and the corresponding oxazolones [69,70], imidazoles [71][72][73], isoxazoles [74][75][76], pyrazoles [38,[77][78][79]), or three (thiadiazole [80]) heteroatoms (Fig. 6).…”
Section: H Ete Rocyclesmentioning
confidence: 99%
“…Examples of central heterocycles include 5-or 6-membered rings that contain one (thiophenes [35][36][37], pyrroles [59][60][61], furans [62,63] and pyridines Pyrroles Eurans 2(5H)-Furanones Thiazo1es 21 [64][65][66]), two (thiazoles [67,68], oxazoles and the corresponding oxazolones [69,70], imidazoles [71][72][73], isoxazoles [74][75][76], pyrazoles [38,[77][78][79]), or three (thiadiazole [80]) heteroatoms (Fig. 6).…”
Section: H Ete Rocyclesmentioning
confidence: 99%
“…The medical importance of pyrazole derivatives is indicated by the large number of reports documenting their various biological activities, such as reported antitumor [16 -18], anti-inflammatory [19,20], ulcerogenic [21], antiviral [22], immunosupressant [23], and antimicrobial activities [17, 24 -27]. Some members of this class of compounds have also been investigated for their local anaesthesic and antiarrhythmic [28], herbicidal [29], and molluscicidal [30] properties.…”
Section: Introductionmentioning
confidence: 99%
“…The IC 50 values of diclofenac for COX-1 and COX-2 were 1.57 and 1.1 ÌM, respectively [9]. While screening for inhibitors of platelet aggregation, Ochi et al [10][11][12] have found that FR122047 is a selective COX-1 inhibitor and FR188582 is a selective COX-2 inhibitor. The authors further reported that in recombinant human COX enzyme assays, IC 50 values of FR122047 for COX-1 and COX-2 were 0.028 and 65 ÌM, respectively (2,300 times more selective for COX-1 than COX-2), and IC 50 values of FR188582 for COX-1 and COX-2 were 100 and 0.017 ÌM, respectively (over 6,000 times more selective for COX-2 than COX-1) [10,12].…”
Section: Introductionmentioning
confidence: 99%
“…While screening for inhibitors of platelet aggregation, Ochi et al [10][11][12] have found that FR122047 is a selective COX-1 inhibitor and FR188582 is a selective COX-2 inhibitor. The authors further reported that in recombinant human COX enzyme assays, IC 50 values of FR122047 for COX-1 and COX-2 were 0.028 and 65 ÌM, respectively (2,300 times more selective for COX-1 than COX-2), and IC 50 values of FR188582 for COX-1 and COX-2 were 100 and 0.017 ÌM, respectively (over 6,000 times more selective for COX-2 than COX-1) [10,12]. In the present study, we examined in vivo effects of the intravenous administration of FR122047 and FR188582 on PGE 2 -induced aqueous flare elevation and mRNA levels for COX-1 and COX-2 in the iris-ciliary body after treatment by these agents in pigmented rabbits.…”
Section: Introductionmentioning
confidence: 99%